Structural Breaks and Causality Relationship between Economic Growth and Energy Consumption in Saudi Arabia - Banafea, Waheed A. (International Journal of Energy Economics and Policy, 2014)
The purpose of this paper is to empirically investigate the short and long run causality between economic growth and energy consumption in Saudi Arabia during the period of 1971-2012 using the Gregory and Hansen (1996) cointegration procedure and error-correction models. The results of the unit root tests with structural breaks indicate that total energy and gas consumption are stationary in levels. Thus, we dropped these variables from the cointegration and causality analysis. The stable long run relationship between real GDP and oil consumption is detected by both stability and cointegration tests. The estimated breakpoints correspond with the period of 1974-1985 during the oil boom. The causal relationship is found between real GDP and oil consumption in both the short and long run. We found short run unidirectional Granger causality running from real GDP to oil consumption. However, the long run unidirectional Granger causality is detected from oil consumption to real GDP. Therefore, the energy conservation policy in the long run should be designed with caution, since energy is considered an engine of GDP growth. Keywords: Energy consumption; Structural breaks; Causality; Saudi Arabia JEL Classifications: C20; Q43; Q48